2021
DOI: 10.3390/ijerph18126553
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes on Cardiac Function in Patients with High Blood Pressure

Abstract: Background: Although the combination of high blood pressure (HBP) and type 2 diabetes (T2DM) increases the risk of left ventricular (LV) dysfunction, the impact of T2DM on LV geometry and subclinical dysfunction in hypertensive patients and normal ejection fraction (EF) has been infrequently evaluated. Methods: Hypertensive patients with or without T2DM underwent cardiac echocardiography coupled with LV global longitudinal strain (GLS) assessment. Results: Among 200 patients with HBP (mean age 61.7 ± 9.7 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Diseases reportedly associated with impaired GLS include HT, type 2 DM associated with obesity, and renal insufficiency [ 1 , [10] , [11] , [12] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diseases reportedly associated with impaired GLS include HT, type 2 DM associated with obesity, and renal insufficiency [ 1 , [10] , [11] , [12] ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that GLS is impaired in aged, female, and overweight patients. [ 5 , 6 ] Several diseases have been associated with impaired GLS, including hypertension (HT), diabetes mellitus (DM), renal insufficiency, cardiomyopathies, and valvular heart disease (VHD) [ 1 , [7] , [8] , [9] , [10] , [11] , [12] , [13] ]. In patients with HT, impaired GLS is reportedly associated with concentric and dilated LV hypertrophy (LVH) patterns, independent of demographic and clinical parameters [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, elevated ECV is associated with both decreased LV global function and LV remodeling in patients with HT [ 35 ]. Bendiab and colleagues investigated the impact of concomitant T2DM on subclinical cardiac function in a cohort of hypertensive patients and found that LV geometry and subclinical LV function as assessed with GLS were more impaired in hypertensive patients with T2DM than in those without T2DM; after adjustment for BP and BMI, T2DM remained an independent predictor of GLS decline (odds ratio = 2.26; 95% confidence interval, 1.11–4.61; p = 0.023) [ 36 ], which is consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from these studies highlighted the overrepresentation of cardiovascular risk factors such as obesity, smoking, diabetes, and hypertension in the Russian population (2) which correlates with reduced cardiac function (9). Known factors like blood pressure, diabetes, body mass index (BMI), age, and sex are known to affect both systolic and diastolic cardiac functions (10,11). However, the speci c in uence of these factors on cardiac function within Russian and Western European populations remains unclear.Strain-rate (SR) imaging by two-dimensional speckle-tracking echocardiography (STE) is sensitive and speci c unmasking latent systolic and diastolic dysfunctions (12).…”
mentioning
confidence: 99%